Alti n coatings rich in al produced by pvd from a metal target
Patent Information
- Application Number
- CN202180066641.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-29
- Filing Date
- 2021-09-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-09-29
AI Technical Summary
然而,迄今为止所有这些提出的方法都具有一些缺点
Smart Images

Figure CN116568853B_ABST
Abstract
Description
[0001] This invention relates to an Al-rich AlTiN coating (hereinafter also referred to as an Al-rich AlTiN coating, Al-rich AlTiN layer, or Al-rich AlTiN film) produced from a metal target by physical vapor deposition (PVD) and a method thereof.
[0002] The present invention also relates to a coating system comprising or including one or more Al-rich AlTiN layers of the present invention described above.
[0003] The Al-rich AlTiN coating according to the present invention should be understood as a coating composed of aluminum (Al), titanium (Ti) and nitrogen (N), or a coating containing aluminum (Al), titanium (Ti) and nitrogen (N) as the main components.
[0004] In this document, the use of the term "Al, Ti, and N as major components" in the context of an Al-rich AlTiN layer specifically refers to the fact that, if the total chemical elemental composition of the Al-rich AlTiN layer is determined on an atomic percentage basis, considering all chemical elements contained in the Al-rich AlTiN layer, the sum of the contents of Al, Ti, and N in the Al-rich AlTiN layer as atomic percentage concentrations corresponds to a value greater than 50 atomic% (i.e., a value from >50 atomic% to 100 atomic%), preferably greater than 75 atomic% (i.e., a value from >75 atomic% to 100 atomic%), and more preferably equal to or greater than 80 atomic% (i.e., a value from 80 atomic% to 100 atomic%).
[0005] In this document, the term “Al-rich” is specifically used to indicate that the aluminum (Al) content in the corresponding Al-rich AlTiN layer is equal to or preferably greater than 70 atomic percent if only Al and Ti are considered to determine the chemical elemental composition in atomic percentage (i.e., Al [atomic %] / Ti [atomic %] ≥ 70 / 30). Background Technology
[0006] AlTiN coatings with Al content exceeding 75 atomic percent (relative to Ti) synthesized via LP-CVD are known to exhibit cubic crystal structures and columnar microstructures. These types of coatings are also known to be comparable to coatings with lower Al content, such as PVD-based Al... 0.67 Ti 0.33 Compared to the N coating, it exhibits superior wear protection.
[0007] Historically, it is well known that PVD methods, such as arc deposition and reactive magnetron sputtering, can be used to produce metastable cubic (B1 crystal structure) AlTiN layers with a maximum of 70 atomic % Al.
[0008] In addition, some publications have proposed possible methods to increase the metastable solubility limit of Al to over 70 atomic percent. However, all of these proposed methods to date have some drawbacks.
[0009] Purpose of the invention
[0010] The purpose of this invention is to provide an Al-rich AlTiN coating and a method for producing the same, which overcomes or mitigates the shortcomings of the prior art.
[0011] If an Al-rich AlTiN coating is applied to a cutting tool, the Al-rich AlTiN coating should preferably exhibit a cubic phase, high hardness, appropriate compressive stress, and coating microstructure, which preferably allows for high wear resistance and improved cutting performance.
[0012] Another object of the present invention is to provide a flexible and reliable method for producing the Al-rich AlTiN coating of the present invention. Summary of the Invention
[0013] The object of the present invention is achieved by providing a method for producing an Al-rich coating for a coating substrate as described in this specification and as claimed in claims 1 to 5. Furthermore, the object of the present invention is achieved by producing an Al-rich AlTiN coating as described in this specification and as claimed in claims 6 to 10, and a substrate coated with such an inventive coating.
[0014] This invention specifically relates to a coating that contains only Al, Ti, and N, or contains Al, Ti, and N as main components, wherein when only these elements are considered, the chemical elemental composition of the coating by atomic percentage is given by formula (Al a Ti b ) x N y Given that a and b are the atomic concentrations of aluminum and titanium, respectively, only Al and Ti are considered to calculate the elemental composition of the layer, where a + b = 1 and 0 ≠ a ≥ 0.7 and 0 ≠ b ≥ 0.2, and where x is the sum of the concentrations of Al and Ti, and y is the atomic concentration of nitrogen, only Al, Ti, and N are considered to calculate the elemental composition of the layer, where x + y = 1 and 0.45 ≤ x ≤ 0.55, where:
[0015] ● Coating display:
[0016] ○90% or more of the fcc cubic phase, and
[0017] ○ 2.5 GPa or greater, for example, compressive stress of 2.5 GPa to 6 Pa.
[0018] For applications requiring relatively high compressive stress, a compressive stress of 4 to 6 Pa is preferably preferred. Furthermore, the present invention specifically relates to a method for forming a coating on a substrate surface according to claim 1, wherein:
[0019] ● Inside the vacuum coating chamber, a coating is synthesized using reactive PVD cathodic arc evaporation technology, wherein:
[0020] - Nitrogen gas is introduced into the vacuum coating chamber as a reactive gas.
[0021] - Use at least one arc evaporation source, which includes target material operating as a cathode to evaporate the target material.
[0022] - The target material is composed of or contains Al and Ti as major components. If only the atomic percentage content of Al and Ti in the target material is considered, the ratio of Al [atomic %] to Ti [atomic %] in the target material is 70 / 30 or greater, i.e., Al [atomic %] / Ti [atomic %] ≥ 70 / 30, preferably 70 / 30 ≤ Al [atomic %] / Ti [atomic %] ≤ 90 / 10.
[0023] - This method involves the reactive deposition of titanium aluminum nitride resulting from the reaction between aluminum and titanium from the target material and nitrogen gas introduced into the coating chamber as a reactive gas.
[0024] - The reactive deposition of aluminum titanium nitride is performed as follows.
[0025] i. Deposition temperature at less than 360°C, preferably as low as possible, for example, 150°C to 250°C.
[0026] ii. At a nitrogen partial pressure of less than 3 Pa, preferably less than 2 Pa, more preferably less than 1.5 Pa, and in any case above 0.05 Pa, preferably 0.1 Pa to 1.3 Pa, more preferably 0.1 Pa to 0.9 Pa, it is just sufficient to form a stoichiometric nitride compound.
[0027] iii. By using the method corresponding to -250V≤U b Within the range of ≤-30V, preferably corresponding to -200V≤U b Within the range of ≤-40V, more preferably corresponding to -200V≤U b Bias voltage U in the range of ≤-60V b .
[0028] The inventors have discovered that using low pressure within the aforementioned suggested range, combined with other process parameters within the suggested range, particularly low process temperature (also known as deposition temperature or substrate temperature during the coating process), allows for the formation of cubic phase fcc for high Al concentrations (Al [atomic %] / Ti [atomic %] ≥ 70 / 30), but the arc discharge may become unstable. Therefore, the inventors propose stabilizing the arc discharge by using an improved magnetic field at the arc source. With this improved magnetic field, a higher discharge voltage can be obtained when using a low nitrogen partial pressure, leading to a stable method. Furthermore, in this way, by using a low nitrogen partial pressure, the inventors are able to produce an Al-rich aluminum titanium nitride coating according to the invention, exhibiting a very small amount of droplets, resulting in a very smooth surface of the coating of the invention.
[0029] According to a preferred embodiment of the method of the present invention as described above, the arc evaporation source operates by generating an arc discharge with a discharge voltage greater than 30V, particularly 30V to 50V, which is possible despite low nitrogen partial pressure. Typically, the discharge voltage decreases when low nitrogen partial pressure is used.
[0030] Another advantage obtained by using a discharge voltage of >30V is that the surface of the target material (e.g., one or more AlTi targets) that is nitrided or partially nitrided due to the reaction of the target material with nitrogen present on the target surface during the coating process can be evaporated.
[0031] Furthermore, the inventors suggest that the dissipated electrical power (resulting in heat load) should remain near the target surface and should not be dissipated into the substrate to be coated, in order to reduce the heat load in the substrate. In this way, the process temperature can be kept low.
[0032] Therefore, preferably, the method is carried out using one or more arc evaporation sources described by Krassnitzer in document PCT / EP2020 / 068828 (International Publication No. WO2021 / 001536A1), which is incorporated herein by reference. In this way, a reactive PVD coating method can be performed to produce an Al-rich AlTiN coating (as described above, with an Al content greater than 75 atomic%), for example, by applying an arc current of 200 A to the target while obtaining a discharge voltage greater than 30 V (e.g., 30 V to 50 V) in the arc discharge, but maintaining a contribution of less than 20% of the electrical power causing heating of the substrate (substrate heating should be understood herein as the thermal load in the substrate to be coated). In many cases, the preferred source current of 200 A or substantially 200 A should not be construed as a limitation of the invention in every case. The source current can vary depending on the chemical composition of the arc source and the target used. As an example available, it can be from 120 A to 200 A.
[0033] An AlTiN coating with Al > 75% (e.g., having a chemical elemental composition in (Al) 76 Ti 33 )N to (Al 90 Ti 10 The coatings in the range of N are preferably produced according to the invention by using low temperature (i.e., low process temperature during the coating process), low gas pressure for obtaining high energy input from ions (in this context, low gas pressure specifically refers to low nitrogen partial pressure - preferably nitrogen is introduced into the coating chamber only as a process gas and reactive gas during the coating process) and high negative bias, which grow in a cubic structure (or grow in a cubic structure to at least 90%) and have high hardness.
[0034] The inventors have discovered that in Al-rich AlTiN layers, the combination of Al and Ti in the above-mentioned ratio (which means Al[atomic%] / Ti[atomic%] ≥ 70 / 30, preferably Al[atomic%] / Ti[atomic%] > 70 / 30, more preferably 90 / 10 ≥ Al[atomic%] / Ti[atomic%] ≥ 80 / 20) greatly contributes to improved wear protection of tools and / or components.
[0035] Furthermore, the present invention relates to coating systems comprising one or more Al-rich AlTiN coatings of the present invention.
[0036] The method of the present invention for producing the Al-rich AlTiN coating of the present invention described above can also be modified by using, for example, additional targets and / or additional reactive gas flows to produce other types of coatings in combination with the Al-rich AlTiN coating of the present invention, so as to produce different coating systems, such as multilayer and / or gradient coating systems.
[0037] Furthermore, reactive PVD coating methods, employing a metal target and simultaneously introducing N2 gas into the coating PVD chamber / apparatus, are crucial for hard PVD coatings with complex coating structures / designs, such as nanolayers and / or multilayer portions of a single coating. PVD coating solutions for hard coatings on tools and / or components are preferred. Preferably, the coating solution should possess a combination of desired coating properties, such as microstructure, texture, elastic modulus, hardness, and stress, with a thickness not limited to only 50 nm or less, and general (not very limited) coating properties, such as a single-crystal grain orientation or very limited low residual compressive stress. Specifically, the coating solution should also be able to improve the properties of AlTiN with an Al content below 70%, as this material system has attracted considerable attention in PVD hard coatings and thus improves, for example, the wear resistance of tools during cutting.
[0038] The Al-rich AlTiN coatings and / or coating systems according to the present invention (i.e., including Al-rich AlTiN coatings according to the present invention) exhibit excellent mechanical properties and are expected to have a beneficial set of properties to provide superior performance for tools and components subjected to wear and stress collectives.
[0039] The above-mentioned invention (Al) a Ti b ) x N y The layer exhibits a preferred face-centered cubic structure. Importantly, the present invention describes a method for producing the Al-rich AlTiN coating of the present invention by reactive physical vapor deposition (PVD), which involves arc discharge of a metallic AlTi target having more than 70 atomic% and less than 100 atomic% Al (preferably 75 atomic% to 90 atomic%), and by simultaneously introducing N2 (nitrogen) gas into the coating PVD chamber / apparatus.
[0040] To better understand the present invention, examples, tables, and drawings will be used to describe it in more detail below. However, these examples, tables, and drawings should not be construed as limiting the present invention, but only as specific examples and / or preferred embodiments of the present invention.
[0041] As described below, an example of the Al-rich AlTiN layer deposited according to the present invention was carried out using a cathodic arc evaporation method at a process temperature of 200°C (hereinafter, the term "process temperature" specifically refers to the set temperature during the coating deposition process) and a low nitrogen partial pressure of less than 1.5 Pa. An AlTi target with an elemental composition of 80Al / 20Ti (atomic percent) was used as the source of Al and Ti materials, and the target was operated as the cathode by applying an arc current of 200 A and applying different substrate bias voltages and pressures for each example.
[0042] Table 1 presents five examples of such deposition methods with detailed process parameters.
[0043] The properties of the Al-rich AlTiN coatings obtained by the methods given in Examples 1-5 are shown in Figures 1-5. Attached Figure Description
[0044] Figure 1: (a) SEM cross-sectional image of the Al-rich AlTiN coating deposited according to Example 1 of the present invention, and (b) spectral diagram of the original deposited film.
[0045] Figure 2: (a) SEM cross-sectional image of the Al-rich AlTiN coating deposited according to Example 2 of the present invention, and (b) spectral diagram of the original deposited film.
[0046] Figure 3: (a) SEM cross-sectional image of the Al-rich AlTiN coating deposited according to Example 3 of the present invention, and (b) spectral diagram of the original deposited film.
[0047] Figure 4: (a) SEM fracture cross-sectional image of the Al-rich AlTiN coating deposited according to Example 4 of the present invention, and (b) spectral diagram of the original deposited film.
[0048] Figure 5: (a) SEM cross-sectional image of the Al-rich AlTiN coating deposited according to Example 5 of the present invention, and (b) spectral diagram of the original deposited film.
[0049] Figure 1(a) , 2(a) 3(a), 4(a) and 5(a): SEM fracture cross-sectional images of Al-rich AlTiN monolithic coatings deposited in five examples of methods with the parameters given in Table 1, including Young's modulus (E), hardness (H) and Al content measured in the deposited films.
[0050] Figure 1(b) , 2(b) 3(b), 4(b), and 5(b): XRD patterns of the original deposited films of five examples of Al-rich AlTiN coatings deposited by the method with the parameters given in Table 1.
[0051] Table 1: Coating parameters for coating deposition in Examples 1-5
[0052] 1 AlTi 80 / 20 200℃ 200A 0.3Pa -150V 2 AlTi 80 / 20 200℃ 200A 0.5Pa -120V 3 AlTi 80 / 20 200℃ 200A 0.3Pa -100V 4 AlTi 80 / 20 200℃ 200A 0.5Pa -100V 5 AlTi 80 / 20 200℃ 200A 0.3Pa -120V
[0053] The membrane structure was analyzed by X-ray diffraction (XRD) using a PANalytical X′Pert Pro MPD diffractometer equipped with a CuKa radiation source. Diffraction patterns were collected using Bragg-Brentano geometry. Micrographs of the fractured cross-section of the membrane were obtained using a FEGSEM Quanta F 200 scanning electron microscope (SEM).
[0054] The hardness and indentation modulus of the undisturbed deposited samples were determined using an ultramicroindentation system equipped with a Berkovich diamond tip. The test procedure included a normal load of 10 mN. Hardness values were evaluated according to the Oliver and Pharr method. Therefore, we ensured that the indentation depth was less than 10% of the coating thickness to minimize substrate interference.
[0055] Figure 1(a) , 2(a) Images 3(a), 4(a), and 5(a) show SEM micrographs of the fracture cross sections of the films of Examples 1–5 and coating properties: elastic modulus (Young's modulus), hardness, and Al content.
[0056] Figure 1(b) , 2(b) Figures 3(b), 4(b), and 5(b) show the XRD patterns of the original deposited films of Examples 1-5, and those XRD patterns indicate a face-centered cubic crystal structure in all coatings. The figures particularly show the changes in microstructure and the presence of a small amount of wurtzite phase when the coatings of the present invention are processed with the different process parameters shown in Table 1.
[0057] To produce the Al-rich AlTiN-based films of the present invention, the inventors used a reactive arc deposition method on a metal target having at least 70 atomic% Al, wherein the inventive combination of deposition parameters was selected based on the following understanding:
[0058] a) Target: Select the arc discharge current, magnetic field distribution, and intensity to achieve the desired plasma state for forming a film-forming material composed of single-charged and multi-charged ions of Al, Ti, and N.
[0059] b) Substrate: The bias voltage is high enough to increase the kinetic energy, thereby increasing the quenching rate of incident ions at the film growth front. At the same time, the substrate temperature is low enough to freeze the migration of adsorbed atoms at the growth front.
[0060] c) General: The nitrogen pressure is controlled within a desired window, which is low enough to reduce the number of nitrogen ions, thereby suppressing the nucleation of the hexagonal phase caused by the remixing effect induced by gas ions on the growth surface, and the nitrogen pressure is high enough to form stoichiometric AlTiN films.
[0061] By optimizing the aforementioned process of arc deposition, the thermodynamically favorable nucleation of the hexagonal phase is suppressed at the growth surface, thereby increasing the metastable solubility of Al in c-AlTiN to a higher concentration of over 75 atomic percent (e.g., 80 atomic percent).
[0062] Other miscellaneous items
[0063] Generally, the intention is that optional claims—when the time may have come—independent of or attached to the original claims, protect the layer and / or method according to one or more (combined) paragraphs below:
[0064] A coating comprising Al, Ti, and N as main components, and having a structure according to formula (Al a Ti b ) x N yThe chemical elemental composition of these elements by atomic percentage, wherein a and b are the atomic concentrations of aluminum and titanium, respectively, and the elemental composition of the layer is calculated considering only Al and Ti, wherein a+b=1 and 0≠a≥0.7 and 0≠b≥0.2, and wherein x is the sum of the concentrations of Al and Ti, and y is the atomic concentration of nitrogen, and the elemental composition of the layer is calculated considering only Al, Ti and N, wherein x+y=1 and 0.45≤x≤0.55, characterized in that: the coating exhibits: 90% or more of fcc cubic phase, and compressive stress of 2.5 GPa or greater, preferably 2.5 GPa to 6 GPa.
[0065] A method for producing a coating according to the foregoing paragraph on a substrate surface, characterized in that the coating is synthesized inside a vacuum coating chamber using a reactive PVD cathodic arc evaporation technique, wherein: nitrogen gas is introduced into the vacuum coating chamber as a reactive gas; at least one arc evaporation source comprising a target material operating as a cathode is used to evaporate the target material, the target material being composed of or containing Al and Ti as major components, wherein the ratio of Al [atomic %] / Ti [atomic %] in the target material is [value missing] if only the atomic percentage content of Al and Ti in the target material is considered. The ratio is 70 / 30 or greater. The method includes reactive deposition of aluminum titanium nitride resulting from the reaction between aluminum and titanium from the target material and nitrogen contained in the coating chamber. The reactive deposition of aluminum titanium nitride is carried out at a deposition temperature of less than 360°C, at a nitrogen partial pressure of less than 3 Pa, preferably less than 2 Pa, more preferably less than 1.5 Pa, by using a bias voltage Ub corresponding to the range of -250V≤Ub≤-30V, preferably corresponding to the range of -200V≤Ub≤-40V, more preferably corresponding to the range of -200V≤Ub≤-60V.
[0066] The special feature of the method described in the previous paragraph is that the arc evaporation source operates by generating an arc discharge with a discharge voltage greater than 30V.
[0067] The method described in the previous paragraph is unique in that the arc discharge is generated in a manner that contributes less than 20% of the electrical power that causes the substrate to heat up.
Claims
1. A method for producing a coated substrate, comprising depositing at least one coating on the surface of the substrate, characterized in that: ● Inside a vacuum coating chamber, the at least one coating is synthesized using reactive PVD cathodic arc evaporation technology, wherein: - Nitrogen gas is introduced into the vacuum coating chamber as a reactive gas. - Use at least one arc evaporation source, which includes a target material operating as a cathode to evaporate the target material. The arc evaporation source operates by generating an arc discharge with a discharge voltage of 30V to 50V. - The target material is composed of or contains Al and Ti as major components. Considering only the atomic percentage content of Al and Ti in the target material, the ratio of Al [atomic %] to Ti [atomic %] in the target material is 70 / 30 or greater, i.e., Al [atomic %] / Ti [atomic %] ≥ 70 / 30. The method involves the reactive deposition of titanium aluminum nitride resulting from the reaction between aluminum and titanium from the target material and nitrogen from nitrogen gas contained in the coating chamber. The reactive deposition of titanium aluminum nitride on the substrate is performed as follows. i. At deposition temperatures below 360°C, ii. At nitrogen partial pressures of 0.1 Pa to 0.9 Pa, using the formula corresponding to -250 V ≤ U b Bias voltage U at the substrate in the range of ≤ -30V b , iii. The formed coating: a. Contains Al, Ti, and N as sole or major components, and has the following properties according to formula (Al a Ti b ) x N y The elemental composition of the coating is calculated by considering only Al and Ti, in terms of atomic percentages, where a + b = 1 and a ≥ 0.7 and b ≥ 0.2, and the elemental composition of the coating is calculated by considering only Al, Ti, and N, where x + y = 1 and 0.45 ≤ x ≤ 0.
55. b. Exhibits 90% or more of the FCC cubic phase, and c. 2.5 GPa or greater compressive stress.
2. The method according to claim 1, characterized in that... Use the corresponding value -200 V ≤ U b Bias voltage U at the substrate in the range of ≤ -40V b .
3. The method according to claim 1, characterized in that... Use the corresponding value -200 V ≤ U b Bias voltage U at the substrate in the range of ≤ -60V b .
4. The method according to claim 1, characterized in that... The compressive stress is 2.5 GPa to 6 GPa.
5. The method according to claim 1, characterized in that... The deposition temperature is between 150°C and 250°C.
6. The method according to any one of claims 1-5, characterized in that... Use the following process parameters within the following range: - The target material shows that the ratio of Al [atomic %] to Ti [atomic %] in the target material is 80 / 20 ≤ Al [atomic %] / Ti [atomic %] ≤ 90 / 10. - Deposition temperature is 180℃ to 220℃. - The partial pressure of nitrogen is 0.1 Pa to 0.9 Pa. - Bias voltage U b The range is from -90 V to -160 V.
Citation Information
Patent Citations
Cathodic arc source
WO2021001536A1
Coated cutting tool
US20190076933A1